Penerapan Tri Hita Karana di Subak Penyalin di Desa Kutuh Kaja, Kecamatan Kerambitan Kabupaten Tabanan - ARIANI, DESAK MADE DENIZA; PITANA, I GDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.2, Desember 2024, 2024)
The application of Tri Hita Karana in Subak Penyalin in the Village of Kutuh Kaja, Kerambitan Sub-district, Tabanan district. Subak is a pillar that concerns social, economic, cultural and religious life for the communication of farmer in Bali. Therefore, the subak irrigation system is implemented on Tri Hita Karana. By learning Tri Hita Karana, humans know how to take good care of nature, Subak Penyalin is one of those who apply Tri Hita Karana that potentially have a positive impact on farmers in implementing it in the fields of individual levels, special ceremonies that carried out according to the beliefs of each farmer, in the pawongan section holding meetings once every three month, mutual cooperation activities in the subak are carried out after the harves, by having  complete organizational structure in the subak, in the palehan section the boundaries of the terriotory owned by the subak are clear, the irrigation network in the subak fairly smooth, and has its own water channel in each tempek subak. Therefor, it was found that the implementation of Tri Hita Karana in the Parahyangan section has been going well because it has carried out the subak ceremony, in the Pawongan section it has been running well because it has carried out mutual cooperation and routine meetings, in the Palemahan section it has been running well because it already has clear land area. Parahyangan, Pawongan, Palemahan. This study aims to determine the application of Tri Hita Karana in Subak Penyalin. Therefore, this study used a qualitative descriptive analysis. Key informants in this study were selected through purposive sampling. The results of the qualitative descriptive analysis show the application of Tri Hita Karana in the Parahyangan section. There are temples in Subak Penyalin from Tri Hita Karana Temple, Uluncarik, Ulun Danu Batur, Ulun Danu Beratan, Puri Tabanan, Pekendungan Tanah Lot, Carrying out ceremonies at the Subak and individual levels, special ceremonies that carried out according to the beliefs of each farmer, in the pawongan section holding meetings once every three month, mutual cooperation activities in the subak are carried out after the harves, by having complete organizational.